Variation of physicochemical and sensory properties during the aging of yerba mate - Santiago A. Holowaty; Sergio A. Surkan; Valeria D. Trela; German D. Byczko; Miguel E. Schmalko (International Journal of Food Studies)
Yerba mate infusion is widely consumed in Argentina, Brazil and Paraguay. One of the processing steps used in Argentina is aging. The following three methods were used to age yerba mate: 1) air humidity and temperature-controlled aging; 2) temperature-controlled aging and 3) no control. The aim of this research was to determine the physicochemical and sensory attribute differences when yerba mate was aged using these three methods. The concentration of caffeine, glucose, fructose, maltose and phenolic compounds and pH diminished in all three aging methods but by different percentages. The sensory attributes did not exhibit uniform behaviour. Astringency remained constant in the first method and diminished in the other two. Bitterness increased in all three methods but by different percentages. Sweetness diminished in all three methods. Notably few correlations were determined between physicochemical and sensory attributes.